دور الوكالات السياحية في الترويج للسياحة الدينية _ دراسة حالة حول وكالة وادي ريغ / الوادي 2019_2020 - عبدالقادر, بوخزنه; يحي, مناوي; محمد السعيد, قمودي (University of eloued جامعة الوادي, 2020)
"تعتبر السیاحة في الوقت الراھن اھم ركائز في اقتصادیات الدول كما لھا تأثیر مباشر في میزانیات الدول ورفع مداخیلھا والسیاحة الدینیة من بین أھم انواع المتعددة للسیاحة في العالم ففي ھتھ المذكرة تخرج لاستكمال متطلبات نیل شھادة ماستر ففي اول المذكرة تطرقنا الى اساسیات حول السیاحة واسباب انتشار السیاحة وانواعھا ومفھومة السیاحة الدینیة ومیزاتھا والمزیج التسویقي للسیاحة الدینیة وتطرقنا بعدھا بعدھا المزیج الترویجي للسیاحة الدینیة التي تضم عدة اعداد للمزیج اول التعریف للمزیج الترویجي السیاحي للحج والعمرة واھمیتھ اھدافھ واھم عناصر المزیج الترویجي للسیاحة .وفي الاخیر قمنا باستبیان في وكالة ریغ للسفر والسیاحة وقدمنا عدة تساؤلات للعدید من الاشخاص لكي تخرج في الاخیر بنتائج الاستبیان ان السیاحة الدینیة للحج والعمرة لھا جوانب مختلفة كل یراھا متطورة الخاص فمنھم من یراھا عبادة خالصة ومنھم من یراھا ایام لتعرف السائح على جوانب دینیة ومنھم من یارھا ترویج عن النفس وغیرھا نسأل الله ان یبلغنا عمرة وحج عاجلا غیر آجلا""Tourism is currently considered the most important pillars in the economies of countries as it has a direct impact on the budgets of countries and raising their incomes and religious tourism among the most important types of tourism in the world. In this memo, it comes out to complete the requirements for obtaining a master’s degree. In the first note, we touched on the basics about tourism and the reasons for the spread of tourism and its types The concept of religious tourism and its advantages and the marketing mix of religious tourism, and after that we discussed the promotional mix of religious tourism, which includes several numbers of the first mix The definition of the promotional tourism mix for Hajj and Umrah and the importance of its goals and the most important elements of the promotional mix of tourism. In the last we carried out a questionnaire in the agency for travel and tourism and presented several questions to many people In order to come out at the end of the results of the questionnaire, the religious tourism of Hajj and Umrah has different aspects, each of which it sees is private. Some of them see it as a pure worship of God, and some of them see it as days to know the tourist on religious aspects, and some of them see it as self-promotion and others. We ask God to inform us of Umrah and Hajj sooner rather than later."
مذكرة ماستر تسويق سياحي وفندقي
Keywords: الترویج السیاجي ، القطاع السیاحي الجزائري، الوكالات السیاحیة في الجزائر; Tourism promotion, Algerian tourism sector, tourist destinations in Algeria